1997
DOI: 10.1177/001440299706400108
|View full text |Cite
|
Sign up to set email alerts
|

Putting Inclusion into Practice: Perspectives of Teachers and Parents

Abstract: Inclusion and parent involvement are considered best practice in early childhood education, but few empirical studies have focused on the practical application of these concepts. This study used qualitative and quantitative methods to investigate the perspectives of parents of children with disabilities and teachers in inclusive settings regarding parent involvement and factors contributing to successful inclusion. Most parents reported that they felt a high degree of involvement on the team, and teachers gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
72
0
13

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(98 citation statements)
references
References 19 publications
11
72
0
13
Order By: Relevance
“…Over the last decade, inclusive models have been implemented in schools across the country based on the idea that children with and without special needs benefit from increased opportunities for interaction and that combined general and special education classrooms can better serve students and increase their educational opportunities (Ferguson, Kozleski, & Smith, 2003). Indeed, research suggests that students with special education needs placed in general education classrooms demonstrate higher levels of social interaction with non-disabled peers, receive more social support than their non-included peers (Fryxell & Kennedy, 1995) and show improved communication skills and social Parental Voice 9 competence (Bennett, DeLuca, & Bruns, 1997). Peltier (1997) concluded that inclusive education promotes all students' social growth and does not negatively impact the academic growth of students without disabilities.…”
Section: Inclusive School Systemsmentioning
confidence: 99%
“…Over the last decade, inclusive models have been implemented in schools across the country based on the idea that children with and without special needs benefit from increased opportunities for interaction and that combined general and special education classrooms can better serve students and increase their educational opportunities (Ferguson, Kozleski, & Smith, 2003). Indeed, research suggests that students with special education needs placed in general education classrooms demonstrate higher levels of social interaction with non-disabled peers, receive more social support than their non-included peers (Fryxell & Kennedy, 1995) and show improved communication skills and social Parental Voice 9 competence (Bennett, DeLuca, & Bruns, 1997). Peltier (1997) concluded that inclusive education promotes all students' social growth and does not negatively impact the academic growth of students without disabilities.…”
Section: Inclusive School Systemsmentioning
confidence: 99%
“…Bennett and colleagues (1997) note that "parents are often dismayed at having to be such strong self-advocates to professionals" (p. 126). Parents can find that the role of advocate puts them in an uncomfortable adversarial relationship with professionals (Bennett, Deluca & Bruns, 1997;Trainor, 2010). Fear of being labeled as 'trouble' or being in the spotlight may hold some parents back from advocacy (Resch et al, 2010).…”
Section: Introduction and Literature Reviewmentioning
confidence: 99%
“…U našem istraživanju vaspitači, između ostalih, navode i ovakve probleme u saradnji sa roditeljima koji su posledica preopterećenosti vaspitača brojem dece u grupi. Ovakva iskustva naših vaspitača svakako treba uzeti u obzir pri osmišljavanju planova za unapređivanje inkluzivne prakse u našim vrtićima, naročito imajući na umu nalaze stranih istraživanja prema kojima je uspešna saradnja i timski rad vaspitača i roditelja jedan od ključnih faktora uspešnosti u radu sa decom sa posebnim potrebama (Bennett et al, 1997;Jewett et al, 1998).…”
Section: Diskusijaunclassified